Dietary intake of mothers who practised traditional confinement during exclusive breastfeeding period - Abdul Basir, Siti Munirah; Abdul Ghani, Radiah; Ibrahim, Muhammad; Khattak, Muhammad Muzaffar Ali Khan; Omar, Muhammad Nor; Mohd Shukri, Nor Azwani (Faculty Of Medicine And Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Nutritional requirements increase during lactation. However, maternal dietary intakes of Malaysian mothers are subjected to restrictions commonly included in traditional postpartum practices. This study aimed to assess the maternal dietary intake status during the recommended six month exclusive breastfeeding (part of which included the traditional confinement) period. Methods: Thirty-two Malay mothers aged 18-35 years, who had delivered full-term (at ≥37 weeks) singleton babies and were exclusively breastfeeding, were included in the study. Maternal dietary intake was assessed using multiple-pass diet recall on Days 10, 30, 60, 90, 120, 150, and 180, postpartum. The average total energy and macronutrient intakes were compared against recommended values. Results: The findings of this study demonstrated that maternal intakes of total energy ranged from 1,500-2,000kcal/day, carbohydrate 189-272g/day, protein 58-72g/day, and total fat 32-70g/day. Total calorie intake was the lowest during confinement period (Days 10 and 30) compared to the rest of the exclusive breastfeeding period. This is similar with total fat consumption. On the other hand, protein intake was the highest during confinement period whereas carbohydrate intake was consistent throughout the six-month period. Despite the increased requirements, intakes of total calories, protein, total fat, dietary fibre, and water, did not meet the recommended values throughout the exclusive breastfeeding period. Conclusion: Mothers’ inability to fulfil their nutritional requirements during exclusive breastfeeding period may be associated with traditional postpartum dietary practices. Dietary advice with consideration for cultural food taboos practiced by local mothers during confinement may help to improve maternal nutritional intakes during this crucial time.